Verification of Carrier Concentration‐Dependent Behavior in Water‐Infiltration‐Induced Electricity Generation by Ionovoltaic Effect. Issue 45 (5th October 2021) - Jin, Huding; Park, Junwoo; Yoon, Sun Geun; Lee, Won Hyung; Cho, Yong Hyun; Han, Junghyup; Yin, Zhenxing; Kim, Youn Sang
Abstract: Water‐infiltration‐induced power generation has the renewable characteristic of generating electrical energy from ambient water. Importantly, it is found that the carrier concentration in semiconductor constituting the energy generator seriously affect the electricity generation. Nevertheless, few studies are conducted on the influence of semiconductor carrier concentration, a crucial factor on electricity generation. Due to this, understanding of the energy harvesting mechanism is still insufficient. Herein, the semiconductor carrier concentration‐dependent behavior in water‐infiltration‐induced electricity generation and the energy harvesting mechanism by ionovoltaic effect are comprehensively verified. A clue to enhance the electric power generation efficiency is also proposed. When 20 µL of water (NaCl, 0.1 m ) infiltrates into a porous CuO nanowires film (PCNF), electric power of ≈0.5 V and ≈1 µA are produced for 25 min. Moreover, the PCNF shows good practicability by generating electricity using various ambient water, turning on LEDs, and being fabricated as a curved one. Abstract : The carrier concentration‐dependent behavior in water‐infiltration‐induced electricity generation is verified by the ionovoltaic effect via energy band theory in semiconductors. By increasing the carrier concentration of the porous CuO nanowire film (PCNF), more ions adsorbed on the surface, thus trapping more holes. Therefore, the difference of PCNF carrier concentration between wet and dry regions increases and the generated electricity enhances.